Changes of meteorological quantities and background activity of ionizing radiation during the passage of mesoscale convective complexes - Nagorskiy, Petr M.; Pustovalov, Konstantin N.; Yakovleva, Valentina S.; Oglezneva, Maria V.; Yakovlev, Grigorii A.; Smirnov, Sergey V.; Vukolov, Artem V.; Belyayeva, Irina V. (Proceedings of SPIE)
The influence of the passage of mesoscale convective complexes (MCC) on γ-ray background and the meteorological quantities in the surface layer are presented in paper. It is noted, that the surface electric field reacts to the passage of the MCC earlier than other measured quantities. This temporary delay is 1 hour. After the rain ended, the elevated radiation background remained for more than 2 hours.